Consistent noisy independent component analysis - Stéphane Bonhomme; Jean-Marc Robin (Centre for Microdata Methods and Practice (cemmap), 2007)
We study linear factor models under the assumptions that factors are mutually independent and independent of errors, and errors can be correlated to some extent. Under factor non-Gaussianity, second to fourth-order moments are shown to yield full identification of the matrix of factor loadings. We develop a simple algorithm to estimate the matrix of factor loadings from these moments. We run Monte Carlo simulations and apply our methodology to British data on cognitive test scores
Keywords: C14; 330; Independant Component Analysis; Factor Analysis; high order moments; noisy ICA; Faktorenanalyse; Fehlerkorrekturmodell; Kognition; Statistischer Test; Großbritannien